2017
DOI: 10.1155/2017/5671860
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Mechanisms of Action of Depside Salt from Salvia miltiorrhiza Using Bioinformatic Analysis

Abstract: Salvia miltiorrhiza is a traditional Chinese medicinal herb used for treating cardiovascular diseases. Depside salt from S. miltiorrhiza (DSSM) contains the following active components: magnesium lithospermate B, lithospermic acid, and rosmarinic acid. This study aimed to reveal the mechanisms of action of DSSM. After searching for DSSM-associated genes in GeneCards, Search Tool for Interacting Chemicals, SuperTarget, PubChem, and Comparative Toxicogenomics Database, they were subjected to enrichment analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…e PubChem website and PharmMapper server were used to predict potential targets for all the predicted targets of bufalin [7]. Additionally, the Draw Venn Diagram website (https://Bioinformatics.psb.ugent.be/webtools/Venn/ ) in the GeneCards database (https://www.Genecards.org/) [8] was used for intersection comparison, and the possible anti-RCC targets of bufalin were acquired from the Gene-Cards database (Figure 1).…”
Section: E Target Of Bufalin Resistance To Rcc Was Obtained Andmentioning
confidence: 99%
“…e PubChem website and PharmMapper server were used to predict potential targets for all the predicted targets of bufalin [7]. Additionally, the Draw Venn Diagram website (https://Bioinformatics.psb.ugent.be/webtools/Venn/ ) in the GeneCards database (https://www.Genecards.org/) [8] was used for intersection comparison, and the possible anti-RCC targets of bufalin were acquired from the Gene-Cards database (Figure 1).…”
Section: E Target Of Bufalin Resistance To Rcc Was Obtained Andmentioning
confidence: 99%
“…Using the Multifaceted Analysis Tool for Human Transcriptome (MATHT, http://www.biocloudservice. com) online tool in "BioCloud" platform, 18 Gene Ontology (GO)_biological process (BP) and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analyses for the DEGs were carried out. The significant threshold was set as P < .05.…”
Section: Differential Expression Analysis and Enrichment Analysismentioning
confidence: 99%
“…Patients receiving early intravenous herbal medicine may have fewer cardiovascular risk factors [2]. Meta-analysis showed that Danshen depside salts, extracted (as dry extract, refined) from the dried root of Danshen Bunge, combined with conventional treatment, were superior to conventional treatment alone in improving angina symptoms; bioinformatics analysis found that Danshen depside salts may target jun, tnf, nfkb, fos, and bcl-2 exerts effects against cardiovascular disease [3, 4]. In view of the antioxidant [5], anti-inflammatory [6], antiapoptotic [7], and cardioprotective effects [8] of Danshen, it is often used in combination with other drugs.…”
Section: Introductionmentioning
confidence: 99%